University-industry relationship: A dual degree model in the light of the German Practice Integration Program - Canto, Cleunisse Aparecida Rauen de Luca (Seven Editora, 2024)
To fill the gap between the teaching-learning process and the business world, academia-industry collaboration is a different strategy in developing innovative learning models. It is a model that allows for joint work, coordinating initiatives to mutually boost innovation, offer opportunities to go from concept to action, encourage entrepreneurship and improve hard and soft skills. In this sense, and aiming at learning based on cooperation, the present study addresses the collaboration between a Professional and Technological Education institution in Brazil and an industry in the metallurgy area that acted in co-creation for the implementation of a higher technology course, following the assumptions highlighted in the conceptual framework for representing knowledge about the dual degree model. The article describes cooperative education and its goals, objectives, and benefits, as well as presents the application of the capabilities define and implement gifts of the proposed dual degree model. DOI:https://doi.org/10.56238/sevened2024.007-051